Maqashid Shariah-Based Sustainability Reporting Analysis at Bank Syariah Indonesia (BSI) - Masruroh, Binti (UNKLAB Business School, 2025)
Sustainability reporting has become a strategic tool for measuring corporate responsibility beyond financial performance, particularly in the banking sector. However, most Islamic banks, including Bank Syariah Indonesia (BSI), still rely heavily on global frameworks such as the Global Reporting Initiative (GRI) and Environmental, Social, and Governance (ESG) without explicitly integrating Islamic values. This study aims to analyze BSI’s 2023 sustainability report using the maqashid syariah framework, which emphasizes five core objectives: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), progeny (hifz al-nasl), and wealth (hifz al-mal). The research employs a qualitative content analysis method by mapping the contents of BSI’s report against these five dimensions. The findings indicate that BSI has successfully addressed four of the five maqashid principles through programs related to religious activities, social health, financial literacy, and inclusive financing. However, the principle of hifz al-nasl remains underrepresented. In conclusion, although BSI demonstrates strong alignment with GRI standards, integrating maqashid syariah more explicitly would enhance the Islamic authenticity of its sustainability reporting and provide a more holistic view of its social and moral commitments.